Los mineros de la Southern - Arciniega Arce, Rosa Silvia (1985)
The Southern Peru Copper Corporation is a private North American company that exploits the Toquepala and Cuajone mining deposits located in the south of the country, in the mountains of the departments of Tacna and Moquegua, respectively. The Toquepala mine officially begins its production in 1960; and Cuajone is inaugurated at the end of 1976. These two mines are connected by rail with the smelter and the port of Ilo, approximately 150 kilometers away. Southern is one of the largest mining companies in the country, concentrating 75% of the national copper production —the main export mining product— and directly employs 4,600 workers distributed in its three areas of operations: the Toquepala, Cauajone and the Ilo smelter.